EFFECT OF BLEACHING EARTH ADDITION IN THE PRETREATMENT OF USED COOKING OIL ON BIODIESEL QUALITY - Devy Arysandi; Ilham Dwi Arirohman; Muhammad Rizky Zen; Aji Suhartoyo (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2026)
Used cooking oil represents a promising alternative feedstock for biodiesel production due to its environmental benefits and economic feasibility. However, its direct utilization is limited by the high free fatty acid (FFA) content, which can interfere with the transesterification process. Therefore, a pretreatment process is required. This research investigates the effect of adding bleaching earth to the pretreatment process of used cooking oil (UCO) on the quality of the biodiesel produced. The research was conducted using a laboratory-scale experimental method with variations in the bleaching earth percentage from 0.5% to 2.0% (w/w). The findings indicate that bleaching earth significantly improves the quality of UCO as a biodiesel feedstock. Nevertheless, excessive addition of bleaching earth may lead to degradation effects and reduced stability of the biodiesel. Optimal performance, corresponding to compliance with SNI 7182:2015, was achieved with the addition of 1.0% bleaching earth. The resulting biodiesel had an acid number of 0.224 mg KOH/g, a density of 851.12 kg/m³, a viscosity of 4.44 cSt, a yield of 72.84% and a calorific value of 46.92 MJ/kg. Additionally, the physical quality, that is color of the biodiesel produced, is bright yellow.